Analysis of the structure and dynamics of polaritons through multidimensional spectroscopy (2024)
ABSTRACT: In this doctoral thesis, the theoretical structure and fast photodynamics of molecular polaritons are investigated by using a sequence of laser pulses according to protocols of two-dimensional nonlinear spectroscopy. The physical system under study is an ensemble of molecular emitters in strong interaction with a mode of quantized radiation in a cavity and subject to dissipative processes due to the surrounding environment. In the semi-impulsive limit and within the rotating wave approximation for laser pulses, conceptually simple and computationally efficient formulas have been obtained for calculating two-dimensional spectra within a perturbative approach. These expressions are useful for any open quantum system characterized by a Liouvillian. Except for the diagonalization of the Liouvillian matrix, our method is entirely general and analytical. A detailed study of linear and nonlinear spectra has been conducted for a finite number of emitter molecules confined in a cavity. Each molecule is treated as a two-level electronic system, subject to vibrational relaxation processes, and the cavity undergoes photon losses. These dissipative processes are added to the dynamics of the Hamiltonian, modeling an open quantum system whose dynamics is solved through a master equation for the density operator. For an ensemble of molecules, the relaxation dynamics of bright polariton states to dark states emerges as a crucial factor in explaining the asymmetry observed in experimental spectral signals. This asymmetry is evident in both the peaks of linear absorption and emission spectra and in the diagonal and cross peaks of two-dimensional nonlinear spectra. The theoretical description developed in this thesis is consistent with recent experimental results conducted on molecular J-aggregates immersed in cavities.